Concerning the system of principles of scientific knowledge for the State power digitization - Emin Najafli (Law and Safety)
On the basis of the latest achievements of theoretical and legal science and other related scientific disciplines, the principles of scientific knowledge for the state power digitalization have been comprehensively studied. The principle of scientific objectivity, applied to the sphere of state power digitalization, acquires some new features, in particular, provides for the consideration of such a variety (form) of digitalization as an objective process that takes place in terms of both promoting and resisting by elements of this process, which takes place in conditions of both assistance and resistance to it by various actors in this process, which makes it difficult to predict the concrete results of the corresponding transformation of state power. This form of digitalization does not occur spontaneously, unlike other forms (in the field of education and economics), but involves its conscious and purposeful management. It has been shown that due to the principle of historicism the processes of state power digitalization in Ukraine are an element of the general civilization process, which occurs in a single trend of world civilization in general and different countries in particular towards the formation of digital civilization. It has been established that determinism is closely related to the previous principles and reveals its role in the study of digitalization of state power in that the very idea of its conditionality by a set of objective and subjective preconditions and reasons makes this process really objective and in demand in the information society. It has been noted that the principle of anthropologism provides an interpretation of digitalization, which is covered by the concept of construct, created and reproduced by the daily actions of legal entities. As a result, digitalization appears as a fragment of human activity to implement certain concepts that involve a conscious and appropriate transformation of state power and it is "the effectiveness of the influence of law on public relations that depends on the subject of law. It has been proved that methodological pluralism in the study of digitalization of state power involves the possibility of effective use of different methods and principles of cognition, combined with the principle of complementarity.